Influencing factors of postoperative urinary tract infection in benign prostatic hyperplasia patients complicated with non-alcoholic fatty liver disease - TIAN Mao, YE Chang (Xin yixue)
Objective To investigate the influencing factors of postoperative urinary tract infection in benign prostatic hyperplasia （BPH） patients complicated with non-alcoholic fatty liver disease （NAFLD）. Methods Clinical data of 159 BPH patients complicated with NAFLD admitted to Xiaogan Hospital affiliated to Wuhan University of Science and Technology from January 2020 to March 2024 were retrospectively analyzed. All patients were divided into the infection （n = 48） and non-infection groups （n =111） according to the occurrence of urinary tract infection. Logistic regression analysis was used to analyze the influencing factors of urinary tract infection. Results Operation time>1 h [OR（95%CI）=3.492 （1.257，9.697）]， history of diabetes mellitus [OR（95%CI）=3.073 （1.075， 8.783）]， time of indwelling catheter after operation>7 days [OR（95%CI）=3.121 （1.093，8.911）]， prostate weight>50 g [OR（95%CI）=3.209 （1.203，8.562）]， abnormal liver function [OR（95%CI）=2.616 （1.126，7.569）]， systemic inflammatory index [SII， OR（95%CI）=1.005 （1.002，1.007）] and serum amyloid A[SAA， OR（95%CI）=1.014 （1.001，1.028）] were the independent influencing factors for postoperative urinary tract infection in BPH complicated with NAFLD （all P < 0.05）. Prognostic nutritional index [PNI， OR（95%CI）=0.968 （0.949，0.987）] was an independent protective factor for postoperative urinary tract infection （P < 0.05）. There were no significant differences in the history of hypertension， age， body mass index （BMI）， maximum urinary flow rate （Qmax）， length of hospital stay and triglyceride （all P > 0.05）. According to the results of multivariate Logistic regression analysis， a prediction model for postoperative urinary tract infection in BPH complicated with NAFLD was established. The area under the receiver operating characteristic （ROC） curve （AUC） was 0.898 （95%CI： 0.849-0.947， P < 0.001）， the specificity was calculated as 0.793， the sensitivity was 0.854， the positive predictive value was 0.641 and the negative predictive value was 0.926， respectively. Conclusions Operation time， history of diabetes mellitus， postoperative indwelling catheter time， prostate weight， abnormal liver function， SII， SAA and PNI are the influencing factors of postoperative urinary tract infection in BPH complicated with NAFLD. This prediction model based on these influencing factors has certain predictive value.